(untitled) (Baltic Journal of Sport and Health Sciences, 2011)
Research background and hypothesis. Health education (HE) is integrated in various modules especially in biology and physical education (PE). Therefore the quality and effectiveness of integrated health education should be analyzed systematically. Research aim. The aim of the study was to examine PE teachers’ perception of health education and social support for HE at their schools. Research methods. The data of convenience sample consisting of 70 physical education teachers (62% were women) from one of the largest Lithuanian cities were analyzed. Respondents ranged in age from 25 to 69 years, average age was 45 ± 11 years. 44.8 percent of participants indicated that they work at school which belongs to the SHE (School for Health in Europe) network. Anonymous questionnaire was developed to assess PE teachers’ health education perceptions and attitudes towards HE. Research results. Only one of ten physical education teachers understood conception of HE and correctly deﬁ ned its main goal. Neither teachers from schools within the SHE network, nor the ones who began their career after Independence fundamentally differed in their understanding and attitudes towards HE from teachers who did not belong to the SHE network or began their carrier before Independence. The ﬁ ndings of the current study demonstrated that in this sample PE teachers’ behavior change – related competencies were not well-developed for the implementation of effective and safe HE. Discussion and conclusions. This pilot study showed that HE perception of PE teachers’ was incorrect and their attitude towards health education should be optimized. No important differences were observed between HE perceptions of teachers in regard of school belonging to SHE network. PE teachers working in SHE school network reported higher social support for HE activities. Keywords: health education, physical education, instrumental competencies.